Social Media and self-identity: Virtual panopticon VS virtual schizophrenia - Snoussi, Thouraya (Opción)
The researcher raised the question about the mechanics of the self-identity building and reshaping through social networking sites. The exploratory study relied on the technique of electronic interviews concluded that Social Media may somehow create a hypothetical virtual prison (Foucault’s panopticon) that affects the psyche of users and lead them to look for the virtual crowd admiration through a deliberate selection of the publications presented in accordance with the requirements of the virtual communities to which they belong. The self-awareness of the virtual crowd is supposed to push social media users to “create” a positive self-identity which is not necessarily identical to their real one.